2021
DOI: 10.1021/acsanm.1c02075
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional-Dependent Effects in Platinum Core–Shell-Based Catalysts for Fuel Cell Applications

Abstract: The oxygen reduction reaction (ORR) activity of platinum catalysts can be affected by tuning the dimension. Experimental reports suggest that one-dimensional platinum catalysts have been identified as efficient ORR catalysts. With this objective, we have modeled one-dimensional Pt90 nanorods (NRs) and investigated the origin of ORR activity. Core–shell effects within one dimension are investigated by modeling 3d metal core-based platinum NRs. Thermodynamic and electrochemical stability-based screening of core–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Hence, identifying a suitable cathode material that synergistically improves the kinetics of both reactions is necessary for improving the performance of LABs. In this direction, many promising electrocatalysts have been reported to accelerate the kinetics of the ORR, which includes the exploration of noble metals (Pt, Au), perovskites, transition metal oxide (Co 3 O 4 , Mn 3 O 4 ), , and carbon-based materials. Among various ORR/OER catalysts, carbon-based nanomaterials have attracted significant attention in Li–air batteries due to their unique properties such as high conductivity, high surface area, porous structure, and most importantly low cost. Within the investigated carbon materials, graphene has been extensively explored as a cathode material due to its high chemical stability and high surface area. Kim et al have prepared a graphene chip as the cathode in an ether-based electrolyte and reported a high Coulombic efficiency of 99% for the first cycle in LABs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, identifying a suitable cathode material that synergistically improves the kinetics of both reactions is necessary for improving the performance of LABs. In this direction, many promising electrocatalysts have been reported to accelerate the kinetics of the ORR, which includes the exploration of noble metals (Pt, Au), perovskites, transition metal oxide (Co 3 O 4 , Mn 3 O 4 ), , and carbon-based materials. Among various ORR/OER catalysts, carbon-based nanomaterials have attracted significant attention in Li–air batteries due to their unique properties such as high conductivity, high surface area, porous structure, and most importantly low cost. Within the investigated carbon materials, graphene has been extensively explored as a cathode material due to its high chemical stability and high surface area. Kim et al have prepared a graphene chip as the cathode in an ether-based electrolyte and reported a high Coulombic efficiency of 99% for the first cycle in LABs.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the alloy nano-catalysts mentioned above, the core/shell separated nano-catalysts exhibit better activity and stability, and improve the efficiency of using noble metals. Bharadwaj et al [126] used theoretical calculations to explore the sizedependent effects of Pt-based core-shell catalysts. The calculations revealed that the constructed model of Cu 48 @Pt 42 NRs had higher ORR activity than that of the Pt 90 NRs.…”
Section: Nanorodsmentioning
confidence: 99%
“…Thus, to improve the BEVs, it is important to develop designs of batteries. Among the next-generation candidates, lithium-air batteries (LABs) have attracted great attention due to their high theoretical energy density which is 10 times higher than LIBs with the use of abundant O 2 at the cathode. , However, the practical implementation of LABs is still far away due to several challenges such as large discharge/charge overpotentials, poor stability of cathode materials, short cycle life, and poor electrolyte stability. The above challenges are caused mainly by sluggish kinetics of the oxygen reduction reaction (ORR), and in this regard, several cathode materials have been reported as cathodes with good stability and ORR catalytic activity. …”
Section: Introductionmentioning
confidence: 99%